Characterising melanoma diagnostic pathways for patients in routine practice using administrative health data in Ontario, Canada: a population-based study - Frances C Wright; Timothy P Hanna; Patti A Groome; Nicole J Look Hong; Meaghan E Mavor; Yuka Asai; Hugh Langley (BMJ Open)
Objective To characterise diagnostic pathways for patients with melanoma in routine practice and compare patient, disease and diagnostic interval (DI) characteristics across pathways.Design Descriptive cross-sectional study using administrative health data.Setting Population-based study in Ontario, Canada.Participants Patients with melanoma diagnosed from 2007 to 2019.Main outcome measures We used latent class cluster analysis to create clusters of patients with similar diagnostic experiences to characterise diagnostic pathways in routine practice. Indicator variables characterised the patient’s keratinocyte carcinoma and dermatologist history, presentation pattern, procedure types, number of visits and procedures, and the activity on the diagnosis date. χ2 tests and Pearson residuals were used. We characterised clusters by the lengths of their DI, primary care subinterval and specialist care subinterval.Results There were 33 371 patients diagnosed with melanoma from 2007 to 2019. We identified four diagnostic pathways: ‘primary care only’ (n=6107), ‘referred to specialist with immediate action’ (n=8987), ‘multiple visits and procedures in specialist care’ (n=11 893) and ‘specialist care only’ (n=6384). Patient, disease and DI characteristics varied across pathways. Pathway types varied regionally. A higher proportion in the ‘primary care only’ pathway lived in rural areas whereas a higher proportion in the ‘referred to specialist for immediate action’ and the ‘specialist care only’ pathways lived in major urban centres. Across pathways, the median DI varied from 1 to 67 days, the median primary care subinterval varied from 1 to 30 days and the median specialist care subinterval varied from 1 to 25 days. Patients in the ‘primary care only’ pathway experienced the shortest DIs, and patients in the ‘multiple visits and procedures in specialist care’ pathway experienced the longest DIs.Conclusions and relevance We identified four melanoma diagnostic pathways. The shortest DI, the ‘primary care only’ pathway, highlights the important role of primary care and the need to reduce the wait for specialists. Diagnostic processes varied across geographical locations. Future research should address reasons for these differences, including whether they are associated with inefficient or inappropriate care.